PENERAPAN ALGORITMA ADVANCED ENCRYPTION STANDARD (AES) UNTUK MENGAMANKAN FILE PADA LAYANAN INFRASTRUCTURE AS A SERVICE (PRIVATE CLOUD STORAGE) STUDI KASUS: FAKULTAS TEKNIK UNIVERSITAS HALU OLEO - Muh.Muchsin Al-As'Ad Mirsyah; LM Fid Aksara; Adha Mashur Sajiah (Informatics Engineering Department of Halu Oleo University, 2019)
A technological development has been affecting the advancement of storage media on computers from time to time. One of the advancement types is the cloud-based store media, in this case, Cloud refers to a metaphor of internet files and data stored on a computer where the users are required to create a Cloud Storage account. Cloud Storage is a storage media that requires access to an internet network. It means as long as the computers are connected to the internet, users no longer need to use a USB flash drive, hard drive or other storage hardware for data storage mobility. However, the security of files and data on Cloud Storage is still very vulnerable to be attacked or retrieved in the database, along with the development of increasingly sophisticated computer technology, the world of information technology requires a stronger and safer cryptographic algorithm. Most recently, the Advanced Encryption Standard (AES) is a secure cipher algorithm for protecting confidential data or information. The results of this study show that the Private Cloud Storage System is able to run well which can be seen from the results of testing this private cloud storage system, all existing menus can run and function properly and from the results of encryption and decryption tests that have been performed on eight types of files show that the testing of six types of files are successful, namely images, .doc, .pdf, .xsls, .ppt, and .txt, whereby those of six types of files are safe based on security testing. For .doc, .xsls, and .txt files when those are opened the files become scrambled. Furthermore, for images, .pdf, and .ppt files an error display will appear when those are opened. Meanwhile, the other two files which are the .mp3 and video type files failed because the algorithm is not able to encrypt and decrypt the file types Keywords— Cloud Computing, Private Cloud Storage, AES, Encryption, Decryption